PEDIATRIC EMERGENCY MEDICINE IN JAPAN: INTERNATIONAL COMPARISON - OHYA, Yukihiro; AKASAWA, Akira (Japanese Journal of National Medical Services, 2002)
Japan is facing serious problems of childhood medical care including the crisis of pediatric emergency care system and overwork of pediatricians. We describe these problems based on comparative study between Japan and foreign nations such as United Kingdom (UK), United States (USA) and Germany, In UK and USA, emergency medicine specialists take care of both adult patients and child patients who visit an emergency room in hospitals, In Germany, pediatricians in training who have a duty for pediatric wards should cope with child patients coming to a hospital emergency room during ex-working hours, but they will be free from the duty when they exceed 40 years old, In Japan, even a skilled pediatric specialist has a duty of working as a primary care physician in an emergency room of a hospital during ex-working hours. But specialist pediatricians in the foreign countries above do not have such a duty as in Japan Specialist nurses treat patients for the triage, but in some hospitals in Japan pediatricians must do triage by themselves. To improve the pediatric emergency care system in Japan, it may be one of the solutions to create the specialist position of emergency medicine and train young doctors for the profession Substantial number of doctors involving child health care in Japan is less than half of that in UK, USA and Germany. Fundamentally, it is an urgent task for us to increase the number of pediatricians in Japan.